Comparison of the adjuvanticity of two adjuvant formulations containing de-O-acylated lipooligosaccharide on Japanese encephalitis vaccine in mice - Ko, Ara; Wui, Seo Ri; Ryu, Ji In; Do, Hien Thi Thu; Lee, Yeon Jeong; Lim, Soo Jeong; Rhee, Inmoo; Jung, Dae Im; Park, Jin-ah; Choi, Jung-ah; Song, Man Ki; Lee, Na Gyong (Archives of pharmacal research, 2018)
Adjuvants are essential vaccine components used to enhance, accelerate, and/or prolong adaptive immunity against specific vaccine antigens. In this study, we compared the adjuvanticity of two adjuvant formulations containing de- O -acylated lipooligosaccharide (dLOS), a toll-like receptor 4 agonist, on the Japanese encephalitis (JE) vaccine in mice. Mice were immunized once or twice at a two-week interval with inactivated JE vaccine in the absence or presence of adjuvant. We found that both the alum- and the liposome-based formulation induced significantly faster and higher serum IgG antibody responses as compared with the non-adjuvanted vaccine after either one or two immunizations. The antibody titers of the mouse immune sera correlated with 50% plaque reduction neutralization test (PRNT 50 ) antibody titers. In addition, the dLOS/liposome formulation was more effective in inducing a Th1-type immune response than the dLOS/alum formulation, as suggested by a strong antigen-specific interferon (IFN)-γ response. Based on these results, we suggest that both alum- and liposome-based adjuvant formulations containing dLOS may be used for the development of JE vaccines with improved immunogenicity.